Termination of pregnancy in a region of Switzerland: a cross-sectional study (Swiss Medical Weekly, 2026)
STUDY AIMS: Data indicate that unintended pregnancy rates are on the decline around the world, largely due to increased access and use of contraception. In a context where data on termination of pregnancy are scarce around the world and access to termination of pregnancy seems to be threatened, it is important to examine the situation in Switzerland. The aim of the article is to present the characteristics of people who had a termination of pregnancy in the canton of Vaud in 2022, and the trends over the last decade.METHODS: Data were collected from the form that gynaecologists are legally required to complete for each termination of pregnancy.RESULTS: In 2022, the rate of termination of pregnancy for resident women was 6.7‰. There were 16.6 terminations of pregnancy per 100 live births. The mean age of women who underwent a termination of pregnancy was 29.6 years (range: 15–47) and the median age was 30 years. Regarding the trends, since 2009, there has been a decrease in the rates of termination of pregnancy among non-Swiss women, while it has increased among Swiss women. A shift between Swiss and non-Swiss women occurred in 2016 with more terminations of pregnancies per 100 live births among Swiss women than non-Swiss women; the opposite was true before 2016.CONCLUSIONS: The rising rate of terminations of pregnancy among Swiss women reflects a trend also observed at the national level. However, the rates at the national and local levels remain among the lowest in the world. To ensure a low rate of terminations of pregnancy, it is important to provide accessible services for everyone and appropriate information according to individual needs and wishes, so that people can choose a contraceptive method that is right for them.